CMOS‐Compatible Controlled Hyperdoping of Silicon Nanowires. Issue 11 (26th March 2018) - Berencén, Yonder; Prucnal, Slawomir; Möller, Wolfhard; Hübner, René; Rebohle, Lars; Böttger, Roman; Glaser, Markus; Schönherr, Tommy; Yuan, Ye; Wang, Mao; Georgiev, Yordan M.; Erbe, Artur; et al.
Abstract: Hyperdoping consists of the intentional introduction of deep‐level dopants into a semiconductor in excess of equilibrium concentrations. This causes a broadening of dopant energy levels into an intermediate band between the valence and the conduction bands. Recently, bulk Si hyperdoped with chalcogens or transition metals is demonstrated to be an appropriate intermediate‐band material for Si‐based short‐wavelength infrared photodetectors. Intermediate‐band nanowires can potentially be used instead of bulk materials to overcome the Shockley–Queisser limit and to improve efficiency in solar cells, but fundamental scientific questions in hyperdoping Si nanowires require experimental verification. The development of a method for obtaining controlled hyperdoping levels at the nanoscale concomitant with the electrical activation of dopants is, therefore, vital to understanding these issues. Here, this paper shows a complementary metal‐oxide‐semiconductor (CMOS)‐compatible technique based on nonequilibrium processing for the controlled doping of Si at the nanoscale with dopant concentrations several orders of magnitude greater than the equilibrium solid solubility. Through the nanoscale spatially controlled implantation of dopants, and a bottom‐up template‐assisted solid phase recrystallization of the nanowires with the use of millisecond‐flash lamp annealing, Se‐hyperdoped Si/SiO2 core/shell nanowires are formed that have a room‐temperature sub‐bandgap optoelectronic photoresponse when configured as a photoconductor device. Abstract : A controlled hyperdoping of Si/SiO2 core/shell nanowires (NWs) is demonstrated. Nonequilibrium dopant Se concentrations are introduced by ion implantation into the upper half of NWs followed by flash lamp annealing. A bottom‐up template‐assisted solid‐phase mechanism is proposed for the recrystallization of the NWs upon implantation. Hyperdoped NWs exhibit a room‐temperature sub‐band gap photoresponse that is mediated by an intermediate band.